1997
DOI: 10.1007/pl00005091
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of the selective dopamine uptake inhibitor GBR 12909, but not cocaine, produces marked decreases in dopamine transporter density

Abstract: The chronic continuous infusion of cocaine produces partial behavioral tolerance to cocaine and tolerance to the inhibition of dopamine uptake by cocaine, without changing dopamine transporter binding. In order to examine more closely the dopaminergic contribution to this effect, the selective dopamine uptake inhibitor GBR 12,909 (30 mg/kg/day), cocaine (50 mg/kg/day), or vehicle, were continuously infused via osmotic minipump, and their effects on the dopamine transporter examined. Drug and vehicle pumps were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…The microdialysis findings with modafinil are much like our previous findings with GBR12909 and its analogspretreatment with these drugs substantially reduces DA release produced by intravenous amphetamine or METH (Baumann et al, 1994(Baumann et al, , 2002. Evidence indicates that GBR12909 and related compounds can prevent DA-releasing effects of METH by persistent occupation of DAT sites or internalization of DAT proteins (Kunko et al, 1997;Baumann et al, 2002). Arguably the most intriguing finding reported here is that modafinil pretreatment diminishes METH-induced ambulation.…”
Section: Discussionsupporting
confidence: 83%
“…The microdialysis findings with modafinil are much like our previous findings with GBR12909 and its analogspretreatment with these drugs substantially reduces DA release produced by intravenous amphetamine or METH (Baumann et al, 1994(Baumann et al, , 2002. Evidence indicates that GBR12909 and related compounds can prevent DA-releasing effects of METH by persistent occupation of DAT sites or internalization of DAT proteins (Kunko et al, 1997;Baumann et al, 2002). Arguably the most intriguing finding reported here is that modafinil pretreatment diminishes METH-induced ambulation.…”
Section: Discussionsupporting
confidence: 83%
“…Kunko et al (1997) observed that subchronic infusion of GBR12909 in rats (30 mg/kg/day for 7 days), which mimics the administration GBR-decanoate shown herein, dramatically reduces the B max for DAT binding in the striatum and nucleus accumbens. This effect is persistent, lasting several days after the cessation of GBR12909 infusion.…”
Section: Discussionsupporting
confidence: 57%
“…ૺ, P Ͻ 0.05 with respect to preinjection control levels. jpet.aspetjournals.org (Rothman et al, 1991;Rothman and Glowa, 1995;Tella et al, 1996;Kunko et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…3 H]dopamine uptake in rat caudate putamen and nucleus accumbens, without changing basal transporter function (Izenwasser and Cox, 1992) or the density of DAT binding sites (Kunko et al, 1997b). Similarly, RTI-117 had no effect on DAT density after a week of continuous infusion.…”
Section: Role Of Dopamine Uptakementioning
confidence: 97%